Use of glucocorticoids in patients with COPD exacerbations in China: a retrospective observational study - Zhang, Jing (Ther Adv Respir Dis, 2018)
BACKGROUND: Acute exacerbations of chronic obstructive pulmonary disease (AECOPD) are common in patients with underlying moderate to severe COPD and are associated with increased health and economic burden. International and Chinese guidelines recommend using glucocorticoids for the management of AECOPD because glucocorticoid therapy has been shown to benefit clinical outcomes. However, only scant data are available for current status of glucocorticoid therapy in hospitalized AECOPD patients in China. The aim of the study was to identify current use of glucocorticoids for the treatment of AECOPD in China. METHODS: This retrospective, multicenter, noninterventional study evaluated the treatment pattern of AECOPD in patients hospitalized from January 2014 to September 2014 at 43 sites (41 tertiary hospitals and two secondary hospitals) in China. The endpoints of the study were the percentage of patients receiving glucocorticoids by different routes of administration, doses and duration, mortality, and the mean length of hospitalization. RESULTS: A total of 4569 patients (90.17%) received glucocorticoids for AECOPD treatment. A combination of nebulized and systemic route was most frequently used (40.51%), followed by using nebulized route alone (38.00%), systemic route alone (15.45%), and inhaled route other than nebulization (6.04%). Furthermore, the most commonly prescribed glucocorticoids of the nebulized, intravenous, inhaled (other than nebulized) and oral route was budesonide (69.4%), methylprednisolone sodium succinate (45.31%), fluticasone propionate (19.54%), and prednisone acetate (11.90%), respectively. The in-hospital mortality rate was 1.24% and the mean length of hospitalization was 12.22 ± 6.20 days (± SD). CONCLUSIONS: Our study was the first study of the treatment pattern of glucocorticoids in the management of hospitalized AECOPD patients in China. Data indicates that there is a gap in the implementation of international guidelines for the treatment of AECOPD in China. Further studies are warranted to clarify the appropriate glucocorticoids strategy for the management of AECOPD to determine the optimal route of administration, dose and duration, and resulting clinical outcomes.